Papel dos neutrófilos na patogênese da cistite hemorrágica induzida por ifosfamida - Dornelas Filho, Amílcar de Figueiredo (2023)
Introduction: Ifosfamide (IFO) is an alkylating cytotoxic agent used in the treatment of gynecological and breast cancer, among others. Among the adverse effects of IFO, hemorrhagic cystitis (HC) stands out, affecting 6-50% of patients. Studies conducted in our laboratory have shown the involvement of various inflammatory mediators in the pathogenesis of HC, such as TNF-α, IL-1β, and nitric oxide, whose pharmacological modulation prevents various inflammatory phenomena, including neutrophil migration. However, the contribution of neutrophils to the development of HC is still unknown. Therefore, the aim of this study was to investigate the role of neutrophils in the pathogenesis of HC. Methods: Female Swiss mice (25-30g) were treated with saline (5 ml/kg, i.p.), FUCOIDAN (a neutrophil rolling inhibitor, 100 mg/kg, i.v.), IFO (400 mg/kg, i.p.), or IFO+FUCOIDAN (10mg/kg; 30mg/kg; and 100mg/kg) followed by water fasting. Additionally, the animals were pre-treated with increasing doses of G-CSF (a neutrophil colony-stimulating factor) for 5 days (100µg/kg, 200µg/kg, 400µg/kg) and IFO (200mg/kg, i.p.) was added, or they were treated with only IFO 200mg/kg or G-CSF 400µg/kg followed by water fasting. After 12 hours, the animals were euthanized by cervical dislocation, and bladder samples were collected for evaluation of bladder wet weight (BWW, mg/20g of animal), analysis of macroscopic lesion criteria (edema and hemorrhage), myeloperoxidase activity (MPO, neutrophils/mg protein), and bladder permeability (BP, pg Evans blue/mg bladder). Results: IFO induced a significant increase (p<0.05) in BWW (52±9.5), edema (3[3-3]), hemorrhage (2[2-3]), MPO (1268±706.2), and BP (111±46) compared to the saline group (BWW: 19.17±3.67; edema: 0[0-0]; hemorrhage: 0[0-0]; MPO: 167.68±59.84; BP: 17.36±2.99). However, these parameters were significantly (p<0.05) reduced by 100mg/kg of FUCOIDIN (BWW: 35.8±9; edema: 1[1-2]; MPO: 552.7±203.6; BP: 38.8±14.6) compared to the IFO group. The groups pre-treated with G-CSF (100µg/kg, 200µg/kg, 400µg/kg) showed a significant increase in BWW (58.8±6.13; 60±3.6; 58±5.34) compared to the BWW of the IFO 200mg/kg group (31.32±4.6). Pre-treatment with G-CSF (200µg/kg, 400µg/kg) + IFO increased the number of neutrophils (1579±314; 1951±257.8) found in the bladder compared to the group treated with IFO (200mg/kg) (961.5±88.5) (p<0.05). When evaluating the microscopic lesion criteria, it was observed that animals pre-treated with 400µg/kg of G-CSF+IFO 200mg/kg induced a significant increase (p<0.05) in leukocyte infiltration scores [3(1-3)] and fibrin deposition [1(0-2)] compared to the group that received IFO (200mg/kg) with leukocyte infiltration score [0.5(0-1)] and fibrin [0(0-1)].Conclusion: Inhibition of neutrophil migration prevented the development of hemorrhagic cystitis, suggesting the role of neutrophils in the pathogenesis of this disease.